CONSTRCUTION WORKERS: PROBLEMS AND ISSUES IN AHMEDABAD - Ratnesh Shah (Journal of Legal Studies & Research, 2016)
India is considered as a land of various religions where people from various countries came and reside in India. Some are high profile, who came to earn big profits, and others are peoples like Construction workers, who came to build the modern India but they themselves never got the shelter to live and proper amenities to stay and grow their children. India’s three crore construction workers are literally the builders of modern India. They build the roads and highways, the railway tracks and airports and ports that connect the vast sub-continent and make India one country, spanning all its distances and diversities. Construction workers are the backbone of the economy as they create the infrastructure necessary for industrial growth. In a globalizing economy, it is they who are constructing the new economic zones, the IT cities; call centres and mega malls that are creating new forms of wealth today. It is they who are laying the cables for a rapidly expanding country-wide telecommunications network. Yet these workers, who are creating these historical monuments and founding the base of the economy, they themselves live in a time warp, bonded with contractual relations, low paid, insecure working conditions, bonded labor etc.